Understanding The Role of Trust Mediation in E-Government Adoption in Citizenship Administration Services Policies in Bantul Regency Using Disdukcapil Smart Application - Kurniawan, Arief; Hartanto, Rudy; Djunaedi, Achmad (National Research and Innovation Agency, Indonesia, 2023)
This study investigates the role of trust in the acceptance of e-government technologies using a modified Unified Model of Electronic Government Adoption (UMEGA) that includes trust as a mediating variable. This study involved 107 respondents from six subdistricts in Bantul Regency, focusing on the use of the Disdukcapil Smart application in e-government citizenship administration services. The findings indicate that performance expectancy, effort expectancy, and perceived security, which are managed by e-government providers, are the determinants of trust. Meanwhile, social influence and privacy risk, which are not managed by e-government providers, are disregarded. Facilitating conditions like citizen-owned infrastructure ease the use of system. The study confirms that trust level influences public participation in bureaucracy, as shown by behavioral intentions in using e-government.